Evolution of Lateral Extra-Articular Tenodesis: Current Perspectives in Primary Anterior Cruciate Ligament Surgery - Calvo, Rafael; Isla, Jorge; Figueroa, David; Edwards, Diego; González, Waldo (Revista Chilena de Ortopedia y Traumatología, 2024)
Introduction Surgical reconstruction is the gold standard treatment for anterior cruciate ligament (ACLR) rupture, aiming to restore normal anatomy, re-establish knee stability, and prevent the development of both meniscal and cartilage pathologies. This surgery has a graft re-rupture failure rate of up to 6-10%, which is why various associated techniques have been described over the last decade to reduce this failure rate. Lateral extra-articular tenodesis (LEAT) is a surgical procedure associated with ACLR, which has been reported to significantly decrease failure rates following primary anterior cruciate ligament (ACL) reconstruction.Objectives To describe the trend and factors associated with the use of extra-articular tenodesis in ACL reconstruction surgery over the last 5 years in a high-volume national clinical center.Methods Retrospective cohort study. An anonymized database consisting of all primary ACL surgeries performed between 2018 and 2023 at our institution was studied. Patients older than 14 years who underwent primary ACL surgery were included, and those who underwent revision surgeries, patients with multi-ligament injuries, or associated fractures were excluded. Descriptive statistics were performed for the variables age, sex, type of graft used, and LEAT performed during surgery. The Prais-Winsten test was used for trend analysis. The Chi-square test was used to analyze the association between sex, type of graft, year, and LEAT. A logistic regression model was constructed with the obtained information.Results A total of 922 patients were analyzed, with a mean age of 30.2 years, 687 of whom were male (74.6%). The most used graft in the sample was hamstring tendons (75.1%). During the study period, LEAT was performed in 14.21% of the participants. The yearly percentage indications were 5%, 8%, 10%, 27%, 17%, and 30% for the period 2018-2023, respectively. The Prais-Winsten test with p < 0.05 showed a significant increase in the use of LEAT over the years. A significant association was found between younger age and LEAT (p < 0.01). No significant association was found between sex and LEAT (p = 0.360), nor between the type of graft and LEAT (p = 0.235).Conclusions In our setting, there is a significant upward trend in the use of LEAT in patients undergoing primary ACL reconstruction surgery. Patients undergoing LEAT are significantly younger, more hyperlax, and participate in contact sports.
Keywords: reconstruction; anterior cruciate ligament; lateral extra-articular tenodesis; failure